1998
DOI: 10.1523/jneurosci.18-19-07687.1998
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell and Single-Channel Analysis of P-Type Calcium Currents in Cerebellar Purkinje Cells of Leaner Mutant Mice

Abstract: The leaner (tgla) mutation in mice results in severe ataxia and an overt neurodegeneration of the cerebellum. Positional cloning has revealed that the tgla mutation occurs in a gene encoding the voltage-activated calcium channel alpha1A subunit. The alpha1A subunit is highly expressed in the cerebellum and is thought to be the pore-forming subunit of P- and Q-type calcium channels. In this study we used both whole-cell and single-channel patch-clamp recordings to examine the functional consequences of the tgla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 43 publications
6
86
1
Order By: Relevance
“…Tg la mutants also showed a slower velocity and frequent failure of propagation of CSD and a much larger reduction of excitatory with respect to inhibitory neurotransmitter release. It has been shown that tg and tg la mutations lead to a decreased P͞Q current density in both native cerebellar neurons and in heterologous expression systems, and that the tg la mutation shifts the activation curve of Ca V 2.1 channels to depolarized voltages and reduces their singlechannel open probability (26)(27)(28). These data support the conclusion that a reduced Ca 2ϩ entry through Ca V 2.1 channels reduces neuronal cortical network excitability and makes the cortex more resistant to CSD.…”
Section: Fhm Mutations Increase Thesupporting
confidence: 53%
“…Tg la mutants also showed a slower velocity and frequent failure of propagation of CSD and a much larger reduction of excitatory with respect to inhibitory neurotransmitter release. It has been shown that tg and tg la mutations lead to a decreased P͞Q current density in both native cerebellar neurons and in heterologous expression systems, and that the tg la mutation shifts the activation curve of Ca V 2.1 channels to depolarized voltages and reduces their singlechannel open probability (26)(27)(28). These data support the conclusion that a reduced Ca 2ϩ entry through Ca V 2.1 channels reduces neuronal cortical network excitability and makes the cortex more resistant to CSD.…”
Section: Fhm Mutations Increase Thesupporting
confidence: 53%
“…Peak current amplitude during the test pulse was normalized and plotted against conditioning pulse voltage to generate the curves in C. phenotype in the relatively short life span of the mouse (17,(20)(21)(22). The absence of motor phenotype in heterozygous or homozygous Sca6 30Q mice also appears to support the notion that SCA6 is not a simple channelopathy because previously described loss-of-function Cacna1a mutants often show early-onset motor phenotypes associated with distinct alterations of Ca 2ϩ channel properties (23,24).…”
Section: Discussionmentioning
confidence: 83%
“…In addition to SCA6, the ␣1A channel is linked to tottering (tg) and leaner (tg la ) mice. The tg la mice have a severe progressive ataxia, and this mutated channel was reported to exhibit a considerably reduced Ca 2ϩ influx into Purkinje cells (27)(28)(29), whereas tg, which expresses mild phenotype, showed a smaller functional alteration (29). Accordingly, the reduced Ca 2ϩ influx by these mutations may account for their ataxic phenotype.…”
Section: Discussionmentioning
confidence: 99%